Metabolomics study of fasudil on cisplatin-induced kidney injury. Issue 11 (19th November 2019) - Xia, Demeng; Lai, Xueli; Wu, Kaiwen; Zhou, Panyu; Li, Lei; Guo, Zhiyong; Xu, Shuogui
Abstract: Fasudil is a derivative of 5-isoquinoline sulfonamide, which is a Rho kinase inhibitor, a wide range of pharmacological effects. Fasudil has been shown to attenuate kidney injury caused by certain substances. In the present study, metabolomic analysis of mouse kidney tissues ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry was used to determine the metabolomic changes in cisplatin-induced kidney injury and the fasudil-induced attenuation of cisplatin-induced kidney injury. Metabolomic profiling of kidney tissues revealed significant differences in metabolites between the control group and the cisplatin group and between the cisplatin group and the fasudil-intervention group. With metabolomic approach, 68 endogenous differential metabolites were found, and multivariate statistical analysis, accurate molecular weights, isotope tracers, mass-spectrometry secondary-fragment information, and standard-reference comparisons were used to identify these substances. Based on these differential metabolites, a metabolic-pathway network was constructed and revealed that fasudil primarily attenuated cisplatin-induced renal injury by modulating lipid and amino-acid metabolism. These results further demonstrate that kidney injury can be induced by cisplatin and, moreover, suggest that fasudil can be used to reduce kidney injury at early stages in patients treated with cisplatin.